إدارة الإنشاءات والبُعد البيئي المستدام: تحسين الكفاءة وتقليل التكاليف والمدة الزمنية للمشاريع في ليبيا (Comprehensive Journal of Science, 2025)
This research aims to evaluate the impact of applying sustainable construction management principles on operational efficiency, cost, and project duration in Libya, with a particular focus on environmental dimensions as a key factor in improving the overall performance of the construction sector. A field research was conducted on three real projects located in the cities of Zliten, Misrata, and Tripoli, using questionnaires and structured interviews with 60 engineers and supervisors.The research employed a descriptive-analytical approach supported by statistical analysis. The findings revealed that projects implementing sustainable management principles recorded a 24% improvement in operational efficiency, a 21% reduction in costs, and a 15% decrease in project duration compared to conventional projects. The results also indicated that the awareness level regarding the importance of sustainable management reached 78% among participants, despite the absence of institutional regulatory frameworks supporting its formal adoption.The research concludes that applying sustainable management practices in Libyan projects is a national necessity to achieve a balance between economic feasibility and environmental protection. It recommends establishing a National Authority for Sustainable Construction and integrating Artificial Intelligence (AI) and Building Information Modeling (BIM) tools into planning and implementation to enhance the environmental and technical performance of projects.
Keywords: Sustainability, Construction Management, Artificial Intelligence, Operational Efficiency, Cost, Libya